Case study Human health versus biosecurity - Al-Sultan I.I. (2015)
This case study is based on realistic true historic events. Since the start of experience and professionalism in the field of Veterinary Medicine which was preferential to maintain specialization and fulfillment to the curia of the writer. The event was in the third academic year of course study in Veterinary Medicine at the Faculty of Veterinary Medicine in the University of Baghdad. That study year was fabulous, although it was hard but without saying it is fruitful to the writer. In that year 1970-1971 the most unexpected hard time is being practiced and never forgotten.